Welcoming Work (Concept: The Journal of Contemporary Community Education Practice Theory, 2022)
In this article, I aim to provide an overview of the Welcoming Association, my ownexperiences and the causes of forced human displacement.I was born to a working-class family in 1960s Tigray, Northern Ethiopia. My fatherdied when I was nine years old and I was brought up by my courageous mother,supported by my uncles. Throughout my secondary school education, I wasbrainwashed by Marxism, Leninism and Maoism. I was taught about the evolution ofsystems from primitive communal society to 20th century communist systems in mymother tongue, Tigrinya.